Repairing the intestinal mucosal barrier of traditional Chinese medicine for ulcerative colitis: a review - Zong, Yichen; Meng, Jie; Mao, Tangyou; Han, Qiang; Zhang, Peng; Shi, Lei (Frontiers in Pharmacology, 2023)
Damage to the intestinal mucosal barrier play an important role in the pathogenesis of ulcerative colitis (UC). Discovering the key regulators and repairing the disturbed barrier are crucial for preventing and treating UC. Traditional Chinese medicine (TCM) has been proved to be effective on treating UC and has exhibited its role in repairing the intestinal mucosal barrier. We summarized the evidence of TCM against UC by protecting and repairing the physical barrier, chemical barrier, immune barrier, and biological barrier. Mechanisms of increasing intestinal epithelial cells, tight junction proteins, and mucins, promoting intestinal stem cell proliferation, restoring the abundance of the intestinal microbiota, and modulating the innate and adaptive immunity in gut, were all involved in. Some upstream proteins and signaling pathways have been elucidated. Based on the existing problems, we suggested future studies paying attention to patients' samples and animal models of UC and TCM syndromes, conducting rescue experiments, exploring more upstream regulators, and adopting new technical methods. We hope this review can provide a theoretical basis and novel ideas for clarifying the mechanisms of TCM against UC via repairing the intestinal mucosal barrier.